PENGARUH MODEL PEMBELAJARAN SINEKTIK DAN PENGUASAAN KOSAKATA TERHADAP KETERAMPILAN MENULIS PUISI SISWA KELAS V SDN 066041 MEDAN - sri ramadhani (JURNAL TEMATIK, 2017)
This study aims to describe the influence of learning model and vocabulary mastery toward writing poetry of Grade V student at SDN 066041 Medan. The population of this study is all students of grade V SDN 066041 Medan Year Learning 2016/2017 consisting of four classes with a total of 123 students. Method used in this research is quasi experimental method (quasi experiment) with 2x2 factorial research design. The results of study found that the synectic learning model is very helpful for student writing poetry with the development of student creativity through analogy. The research findings show that (1) There are differences in poetry writing skills taught by the model of synectic and CTL learning in grade V students of SDN 066041 Medan, (2) There is differences of writing poetry skill which has high vocabulary mastery and low vocabulary mastery in grade V students at SDN 066041 Medan, and (3) there is interaction between synectic learning model and vocabulary mastery of writing poetry skill of grade V student at SDN 066041 Medan.